Cryptocurrency Transactions in the Perspective of Islamic Economic Law - Anggriani, Lulu; Maulana, Defa Gustara; Mahipal, Mahipal (Universitas PGRI Madiun, 2024)
The advancement of the digital era which is increasingly widespread and commonplace has encouraged a shift in transactions that makes various transactions easier. Modern innovation in the digital era has expanded payment methods beyond the traditional use of cash and current accounts (non-physical). Many people utilize cryptocurrency as digital money, but there are unavoidable pros and cons to this technology based on the blockchain protocol. Various arguments have been put forward for and against cryptocurrencies in Indonesia. One argument is that this does not adhere to standard practices for transactions and currencies. Another argument is that the Indonesian government has firmly stated that Bitcoin and similar virtual currencies are not legal tender in the country. The widespread use of digital money in people's lives requires research and analysis from religious and technology experts considering these events and facts. Bitcoin and other cryptocurrency transactions are considered gharar and dharar from an Islamic economic perspective